Few Differences in Metabolic Network Use Found Between Salmonella enterica Colonization of Plants and Typhoidal Mice - Kwan, Grace; Plagenz, Brett; Cowles, Kimberly; Pisithkul, Tippapha; Amador-Noguez, Daniel; Barak, Jeri D. (Frontiers in Microbiology, 2018)
The human enteric pathogen Salmonella enterica leads a cross-kingdom lifestyle, actively colonizing and persisting on plants in between animal hosts. One of the questions that arises from this dual lifestyle is how S. enterica is able to adapt to such divergent hosts. Metabolic pathways required for S. enterica animal colonization and virulence have been previously identified, but the metabolism of this bacterium on plants is poorly understood. To determine the metabolic requirements for plant colonization by S. enterica, we first screened a library of metabolic mutants, previously examined in a systemic mouse typhoidal model, for competitive plant colonization fitness on alfalfa seedlings. By comparing our results to those reported in S. enterica-infected murine spleens, we found that the presence of individual nutrients differed between the two host niches. Yet, similar metabolic pathways, contributed to S. enterica colonization of both plants and animals, such as the biosynthesis of amino acids, purines, and vitamins and the catabolism of glycerol and glucose. However, utilization of at least three metabolic networks differed during the bacterium’s plant- and animal-associated lifestyles. Whereas both fatty acid biosynthesis and degradation contributed to S. enterica animal colonization, only fatty acid biosynthesis was required during plant colonization. Though serine biosynthesis was required in both hosts, S. enterica used different pathways within the serine metabolic network to achieve this outcome. Lastly, the metabolic network surrounding manA played different roles during colonization of each host. In animal models of infection, O-antigen production downstream of manA facilitates immune evasion. We discovered that manA contributed to S. enterica attachment, to seeds and germinated seedlings, and was essential for growth in early seedling exudates, when mannose is limited. However, only seedling attachment was linked to O-antigen production, indicating that manA played additional roles critical for plant colonization that were independent of surface polysaccharide production. The integrated view of S. enterica metabolism throughout its life cycle presented here provides insight on how metabolic versatility and adaption of known physiological pathways for alternate functions enable a zoonotic pathogen to thrive in niches spanning across multiple kingdoms of life.